A Review of Highway Agencies in the South Asia Region - Rohatgi, Rajesh; Bandyopadhyay, Arnab; Gupta, D.P. (World Bank, Washington, DC, 2017)
Explosive growth in demand for passenger and freight transport in the South Asia region, driven by high economic growth, has put the spotlight squarely on ensuring enhanced delivery of infrastructure and services. The objective of the study is to help governments and policy makers in identifying reforms that are required to modernize and strengthen the capacity and performance of their road agencies to deliver large investment programs through performance monitoring as a tool. A review of the highway agencies in the region has been undertaken to suggest: a) indicators to assess their capacities and performance; and b) a roadmap to improve performance in key functional areas of the agencies. The scope of study included a review of a sample of highway agencies from Bangladesh, India, Nepal, Pakistan and Sri Lanka. This sample included national and provincial level highway agencies as well as road corporations. In India, the focus was on the state-level highway agencies. This study also incorporates findings from earlier studies commissioned by the World Bank.